(untitled) ("Temas Sociais" Journal, 2022)
Abstract Following the 2008 financial crisis and with the increase of migrants movements since 2015 the welfare policies across EU are increasingly becoming instruments for limiting mobility of migrants from outside the EU borders. In this article we focus on the implications that asylum policies have for the interventions of social workers and the ethical dilemmas that they face. This article is the result of an exploratory work. Thus, based on the author’s PhD dissertation, as well as resorting to her professional experience as a social worker, she carried out a literature review to identify a set of articles that analyse the practice of Social Work with asylum seekers and refugees and the ethical issues and challenges associated with it. The main goal of this article is to contribute to the reflection on the role of the social worker in safeguarding human rights of this population. Keyword: Refugee, asylum seekers, social work, ethical dilemmas